CREATING THE STANDARD FOR SPECIFIC ENERGY CONSUMPTION AT PALM OIL INDUSTRY - Alfa Firdaus; M Syamsul Ma’arif (Universitas Mercu Buana, 2016)
There is currently no standard for the Specific Energy Consumption (SEC) in the palm oil industry. SEC is a value that can be used as an indicator to measure the optimization level in the use of energy. Indonesia as one of the largest palm oil producing countries requires a standard for energy intensity in the palm oil industry. SEC in palm oil mill is defined in the amount of energy per unit of production (kWh/kg). The classifying method that has been used in this study is K-means cluster analysis with the measurement samples in 14 palm oil mills for 12 months of period. This study has suggested the SEC standard for Indonesian palm oil industry and it is expected to be SEC reference for other studies in the palm oil industry.